Expiratory Carbon Monoxide Levels of Cigarette Smokers in College Environment - Sumarsudi, Karel Handito Syafi; Damayanti, Triya (Jurnal Respirologi Indonesia, 2024)
Background: The impact of smoking is still a huge problem in the world. The use of cigarettes is one of the biggest causes of death that can be prevented. One of the harmful substances of smoking is carbon monoxide (CO). Unfortunately, research comparing CO levels in white and Kretek cigarette smokers among college students in Indonesia has not been conducted. This study aims to determine the relationship of expiratory CO levels in male students who smoke white or Kretek cigarettes at a university in Depok using a CO analyzer and questionnaire.Methods: This is a cross-sectional study design with 108 samples divided into two groups of white cigarette smokers and Kretek cigarette smokers with consecutive sampling techniques. Subjects took the expiratory CO test using a CO analyzer and filled out questionnaires related to smoking and other factors.Results: The study found expiratory CO results in white cigarette smokers at 13.9±8.36 ppm and Kretek cigarette at 13.18±8.79 ppm with no significant relation statistically. The factor that influences the subject's CO expiration is the Brinkman Index (P<0.001) with a weak correlation result and factors that influence the choice of cigarette type, namely pocket money (P=0.023) and age (P=0.015).Conclusion: There was no statistically significant relationship between the average of white cigarette smokers or Kretek cigarette smokers with expiratory CO levels in subjects. This might be due to a more significant effect on the number of cigarettes consumed. Seeing the trend in Indonesia that Kretek cigarettes are relatively cheaper than white cigarettes, money allowance is one of the factors that determine the choice of white or Kretek cigarettes for college students in Depok.